The Use of Spelling in Students' Scientific Articles in Department of Indonesian Language and Literature - Harahap, Muharrina; Anggreini, Heny; Jakaria, Jakaria; Barus, Frinawaty Lestarina; Naelofaria, Salmah (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
This research was conducted to find out the spelling mistakes and the causes of spelling mistakes in scientific articles of students of the Indonesian Language and Literature Department. By knowing this, students will comprise scientific papers that are good and correct, and in accordance with the rules. The method used in this research was descriptive qualitative. The sources of research data were students' scientific articles of the Department of Indonesian Language and Literature, which are the products of team-based projects during Comparative Literature (fifth semester). The researcher chose four scientific articles to obtain the research results to be achieved or called the purposive sampling method. This research used an analytical method, namely the orthographic equivalent method, whose determining tool is writing with the concept of EYD and language errors. The results of this study are that students of the Department of Indonesian Language and Literature still often make Indonesian language mistakes in working on team-based project products in the form of scientific articles. This is due to the lack of understanding of students in the use of spelling in accordance with the rules. Then, students are less careful and lazy in checking the use of spelling. Therefore, students need to get training in writing (the use of spelling and Indonesian language rules) in order to become competent students in their fields according to the profile of graduates (research assistants, academics, and practitioners).